Effect of cracks on the service life of RC structures exposed to chlorides - Nicoletta Russo; Matteo Gastaldi; Luca Schiavi; Alberto Strini; Riccardo Zanoni; Federica Lollini (Acta Polytechnica CTU Proceedings, 2022)
To move towards a more sustainable concrete, the enhancement of its durability is strongly encouraged and, dealing in particular with reinforced concrete (RC), this mainly means to prevent the damage due to environmental actions, e.g. due to chloride-induced corrosion. Therefore, there is the need of models aimed at designing durable structures. Usually the service life design models consider concrete in uncracked condition. In real structures, however, several phenomena can generate cracks on concrete surface, leading to an acceleration of the corrosion of steel rebar. A number of studies have been recently carried out in order to evaluate the influence of cracks on reinforced concrete durability in chloride-contaminated environment, however the knowledge of the effect of cracks on the initiation and propagation periods is still lacking. Furthermore, few studies have considered additional protection strategies, such as the use of stainless steel rebar. In this work, experimental results are presented concerning the influence of cracks on the service life of reinforced concrete structures in order to evaluate if cracks lead to an earlier corrosion initiation induced by chlorides. Prismatic specimens, reinforced with carbon steel and 304L stainless steel bars, were longitudinally cracked and exposed to ponding with 3.5% NaCl solution. The monitoring of corrosion behaviour showed that when cracks reached the steel surface corrosion initiated immediately.